Microbial biomass carbon and nitrogen content in Havana Soil. - Gómez-Jorrin, Luis A. (2012)
This research was carried out to calculate the microbial biomass carbon and nitrogen content in Red Ferralitic Soils from the Havana province, using theg fumigation and extractionh method. For this work soil samples were taken from four different sites (Bainoa, La Salud, Quivican and Guanajay) with different physicalchemicalcharacteristics, including organic matter content which ranged from 2.8 and 5%. The sensibility of the methods employed was asssessed using the mean standard error as statistical parameter. The C content in soil microbialbiomass ranged from 289 and 425 ƒÊg/g of soil (289 . 425mg/kg of soil) and had it a significant correlation by soil organic matter content. On the other hand, N content in soil microbial biomass ranged from 62 and 90 ƒÊg/g of soil(62-90 mg/kg of soil), and had it a signifi cant correlation by soil nitrogen content. The mean standard error of microbial C determinations ranged from 2 and 16, being slightly superior to previous reports, while the mean standard error of the microbial N determinations were among adequate limits. Finally, this methodology was adapted to laboratoryconditions.